Hajléktalanok a rendszerváltásról . Homeless People About the Regime Change in Hungary - Göncz, Viktor (Hungary, 2005)
Verzio FF Submission Short interviews with homeless people who debate the political system in Hungary, and talk about the upcoming regime change.